An Interdisciplinary Framework for Islamic Cognitive Theories - Kaplick, Paul M. (Zygon, 2019)
The Islamic psychology (IP) community in Europe has recently witnessed a heated debate about the credentials required to participate in the theoretical substantiation of IP and Islamically integrated psychotherapy and counseling. This debate has provided convenient circumstances for Muslim psychologists and Islamic scholars alike to rethink their roles within the flourishing movement. Specifically, the discussions hint toward the importance of adopting a collaborative research methodology for IP, in particular for basic research. The methodology of choice will need to define the necessary qualifications and responsibilities of scholars and psychologists in a collaborative research process (personal collaboration) and evince its capability to appropriately marry knowledge and data, diverging research methods, and perspectives, concepts, and theories from Islamic studies and contemporary psychology (content-related collaboration). Here, we devise and offer a case illustration of an Islamic Psychology Basic Research Framework (coined the SALAAM Framework). This framework uses the Institute for Interdisciplinary Studies (IIS) Model of Interdisciplinary Research, developed by the IIS at the University of Amsterdam. Our first aim is to appropriate the IIS model for the IP literature by applying the model's research process phases and technique for the integration of disparate bodies of knowledge-that is, the identification of common ground-to methodological approaches in the contemporary IP literature. Our second aim is to exemplify the devised SALAAM Framework using the relatively unexplored area of Islamic cognitive theories (ICTs), which remain underdeveloped in contemporary psychological literature, primarily because of a lack of commensurability with the nomenclature of contemporary psychology. We thus provide a primer on the potential scope of ICTs. Toward the end of this article, we discuss the potential of the project of interdisciplinary construction of Islamic psychological theory, and the ability of the SALAAM Framework to establish a research program in IP that centers on cognition. We finally offer our reflections on the distinctiveness of Islamic psychologies in comparison to mainstream and Christian psychology.